Problematika Pembelajaran Daring pada Masa Pandemi Covid-19 - Moh. Solehuddin; Nur Wahib (Risda: Jurnal Pemikiran dan Pendidikan Islam, 2021)
The outbreak of the Covid-19 corona virus has greatly changed teaching and learning activities which usually take place face-to-face. Even so, this pandemic was able to accelerate education 4.0..This phenomenon is rife in the world of education during the Covid-19 pandemic, in almost all schools and madrasas. Before the Covid-19 Pandemic, the learning system at this school was carried out face-to-face or directly, although sometimes it also used ICT to support teaching and learning activities so that they were more varied and create a comfortable and fun learning atmosphere, but after the Covid-19 pandemic occurred the The school implements online teaching and learning activities as a preventive effort so that all students and teachers who teach at this school are not exposed to Covid-19. There are several kinds of applications used in this school, including WAG, Hangout, Google Classroom, Zoom and so on